Effect of psychological stress on time and frequency domain parameters of heart rate variability in undergraduate medical students - Sadiq, Noman; Raziq, Hammad; Tahir, Muhammad; Nasir Rajpoot, Noor (Journal of Fatima Jinnah Medical University, 2019)
Background: Psychological stress disrupts student capabilities along with several physiological and psychological processes including functioning of autonomic nervous system. Heart rate variability is an important indicator which reflects the functioning of autonomic nervous system. The objective of this study was to measure and compare the effect of stress on time and frequency domain parameters of heart rate variability among stressed and stress-free medical students. Subjects and methods: This cross-sectional study was carried out at Power lab room, department of Physiology at Islamic International Medical College, Rawalpindi from September 2016 to January 2017. Students were randomly divided into two groups i.e. stressed and stress-free group on the basis of their Depression Anxiety Stress Scale questionnaire score. Ten minutes Electrocardiogram (ECG) of each participant was measured in power lab room and parameters of heart rate variability, including time domain (heart rate and Root Mean Square of the Successive Differences (RMSSD) of R-R intervals) and frequency domain (low frequency (LF), high frequency (HF) and LF/HF ratio) were analyzed by using lab chart 8 pro software. Results: Stress significantly reduces Heart Rate Variability (HRV). Among parameter of HRV, Heart rate, Low Frequency (LF), LF/HF ratio was significantly raised in stress group as compare to stress free group (p<0.05). High Frequency (HF) parameter of HRV was significantly increased in stress free group as compared to stress group (p<0.05). Conclusion: Stress upsurges cardiac sympathetic nerve activity and reduces cardiac parasympathetic nerve activity as reflected by parameters of Heart rate variability.